Author Correction: Impact of hormone receptor status and distant recurrence-free interval on survival benefits from trastuzumab in HER2-positive metastatic breast cancer. Issue 1 (December 2018) - Yang, Hai-Yuan; Ma, Ding; Liu, Yi-Rong; Hu, Xin; Zhang, Jian; Wang, Zhong-Hua; Di, Gen-Hong; Hu, Xi-Chun; Shao, Zhi-Ming
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.